Metafora Dalam Mantra Kidung Montrawedha - Puspitasari, Dhika (LP. Ma'arif Janggan Magetan, 2023)
This study entitled ‘Metaphor in Mantra Kidung Montrawedha’. This mantra is written by Sunan Kalijaga found in the book of Primbon Attasadhur Adammakna. This research explains the types of metaphor based on semantic field. This study uses qualitative descriptive method which is done based on real facts or phenomena. The process of collecting data uses library research technique. This technique explores written sources such as magazine, newspaper, or literature as the data. The result of this study shows that the mantra of Kidung Montrawedha have the types of methaphor are energy, substance, living, and human.